ОСОБЛИВОСТІ ДІЯЛЬНОСТІ НЕУРЯДОВИХ АНАЛІТИЧНИХ ЦЕНТРІВ В УКРАЇНІ (World Science, 2018)
The article provides an overview of the non-governmental analytical environment in Ukraine, represents main stages of the development of non-governmental think tanks and their current state, represents the main features and problems of their functioning, deals with the analysis of information capacity of research centers of Ukraine and their classification, based on the results of recent research conducted within the framework of the Initiative for the Development and Research of Analytical Centers. It describes the position of Ukraine in the annual global ranking of analytical centers 2017 Global Go To Think Tank Index Report's.